Maggot As an Alternative to Organic Waste Management in Kaliboja Village Pekalongan - M. Iqbal Agil Faiq; Muhammad Alghiffary; Namirotun Sa’diah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Pekalongan, 2021)
Organic waste is one of the environmental problems that must be handled properly and correctly so as not to cause other problems. This research aims to analyze the problem of organic waste in Kaliboja village paninggaran district pekalongan using maggot. This was done for 45 days in kaliboja village. Qualitative methods are used in this study with data collection techniques in the form of observation, free interviews, and documentation. The collected data is tested using the completion method when collecting the data. The result of this study is that maggot cultivation can help overcome the problem of organic waste in kaliboja village. Organic waste is managed by making it as maggot feed or Hermetia illucens.